Operation METHODICAL: protecting London’s art during a nuclear attack - Dunkley, Mark (Taylor & Francis, 2025)
On the 6 November 1972, detailed orders were issued by HQ United Kingdom Land Forces for the removal of major national art treasures from London in the event of a nuclear attack on the UK. The codeword METHODICAL was given to this operation. Lessons for evacuating significant works of art from London during the Second World War had been adapted and expanded for re-use during the Cold War, which also saw considerations for collections in both Edinburgh and Cardiff. Given that the international security context has shifted back towards competition and state-on-state conflict from one of international terrorism and state failure in the post-Cold War era, perhaps now is the time to reconsider how nationally important artworks and collections can be safeguarded and their security integrated into homeland defence planning.
Keywords: Cold War; homeland defence; evacuation; British Army; 43 History, Heritage and Archaeology; 16 Peace, Justice and Strong Institutions